P. BOURDIEU'S HABITUS AS A METHODOLOGICAL TOOL FOR STUDYING THE TRANSFORMATION OF A DOCTOR'S IDENTITY IN CONTINUING PROFESSIONAL EDUCATION - Filimonov, Sergey Nikolaevich; Vinogradova, Elena Anatolyevna (Medicine in Kuzbass, 2026)
This article analyzes the methodological potential of Pierre Bourdieu's concept, particularly the concept of “habitus”, for studying the transformation of physician identity under the influence of continuing professional education. It also examines the problem of bridging the gap between the formal requirements and evaluation criteria of continuing professional education and the actual changes in the values and professional identity of medical professionals.The purpose of the study is to uncover the methodological value of Pierre Bourdieu's concept of “habitus” for analyzing the profound changes in physician identity under the influence of continuing professional education.Materials and Methods. The study draws on Pierre Bourdieu's theoretical framework, which includes a system of interconnected categories: «habitus», «field» and “capital”. The primary method utilized is theoretical analysis, aimed at projecting this socio-philosophical concept onto the specifics of continuing professional education.The results and their discussion. Traditional approaches to assessing continuing professional education, focused on formal indicators, ignore an important aspect: changes in the value foundations of the profession. The concept of “habitus” shifts the focus of analysis to the physician's internal dispositions, shaped by previous experience, including clinical experience. The institution of continuing professional education, by translating state healthcare policy, including standardization and cost-effectiveness, creates a new «field» with different rules of the game. The primary motive for physician participation in this field is the struggle for symbolic capital (legitimate status), which often conflicts with traditional professional values. The key mechanism behind these emerging contradictions is the “hysteresis effect” of habitus, that is, its delayed adaptation to abrupt institutional changes. This manifests itself in medical specialists' formal attitudes toward continuing professional education, internal resistance to innovation, and changes in values and identity.Conclusion. Using P. Bourdieu's concept allows researchers and practitioners of continuing medical education to understand the crisis in this field. This approach substantiates the need to consider the hysteresis effect of physician habitus. In practical terms, this means using physician training methods that take into account not only the transfer of new knowledge but also the development of established patterns of professional consciousness. This could manifest itself, for example, in a shift in emphasis to the analysis of clinical cases, where new standards demonstrate their effectiveness within the framework of the familiar logic of “practical sense”.
Keywords: continuing professional education; professional identity; habitus; hysteresis; social field; Pierre Bourdieu; medical personnel